ANALISIS KINERJA KONTRAKTOR TERHADAP KUALITAS PELAKSANAAN PROYEK PEMBANGUNAN GEDUNG DI KABUPATEN SIKKA - Agnes Margareth Natasya Fernandez; Margaretha Yuneta; Triapriono Kaidu (Program Studi Teknik Sipil, 2025)
From the results of the survey conducted for 2 hours and 30 minutes, the maximum parking accumulation was 93 vehicles for motorcycles, the parking volume was 168 motorcycles, the PTO for motorcycles was 0.38 vehicles/plot/hour, and the maximum motorcycle parking index was 38%. This means that the condition of motorcycle parking can still accommodate vehicles because it is less than 100%. Parking Supply at Upp was 21.11 motorcycles, Parking Needs (NP) for motorcycles was 439 parking plots. This study focuses on the analysis of contractor performance and its impact on the quality of building construction project implementation in Sikka Regency. The research method used is quantitative with a survey approach, where data was collected through questionnaires distributed to 35 respondents, including contractors and consultants who have experience in construction projects for the past five years. The results of the analysis show that there are 15 variables that influence contractor performance. Motivation and material factors were found to be dominant factors, with a mean value of 4.638 and 4.65, respectively, indicating that contractor motivation and the quality of the materials used greatly determine the success of the project. In addition, the analysis also identified aspects of project quality, such as timeliness, conformity to specifications, durability, and aesthetics, all of which were in the good category.